Digital Transformation and Resilience of Slovenian SMEs - Marolt, Marjeta; Pucihar, Andreja; Lenart, Gregor; Vidmar, Doroteja; Kljajić Borštnar, Mirjana (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
Digital transformation increases the resilience of micro, small, and medium-sized enterprises by enabling them to maintain their business during disruptions, to streamline processes, and to engage more effectively with customers and suppliers. However, limited resources and skills often prevent them from taking full advantage of digital technologies. Although the use of digital technology is monitored by Eurostat, the European Commission, and the OECD, there is still insufficient research on how micro, small, and medium-sized enterprises have digitally transformed their business in recent years and how resilient they are. Therefore, this study focuses on exploring the digital transformation and resilience of micro, small, and medium-sized enterprises and the differences between them. The survey, based on 159 valid responses, analysed using SPSS, shows certain shifts towards digital transformation in Slovenian micro, small, and medium-sized enterprises. Although most companies already include digitization in their business strategy, there are significant differences between micro, small, and medium-sized enterprises in terms of the degree of digital transformation and resilience achieved.